Protestant Churches, Society and State in China: Past Lessons and Current Prospects - Joseph Tse-Hei Lee (2024)
This article provides an historical overview of Protestantism and Church-state relations in China from the late nineteenth century to the present, focusing prinicipally on two parallel phenomena. The first concerns the transformation of Christianity from a marginalized belief system into a deeply indigenized religious movement. The second phenomenon is the emergence of an indigenous Christian spirituality that provides people with strong spiritual, psychological, and material resources to cope with the multiple overlapping challenges of inequality, and the uncertain encounters with the state which is still suspicious toward grassroots religious ideas and practices. Beginning with an analysis of the Protestant missionary expansion into China, this article discusses the profound challenges facing different Protestant denominational churches and indigenous groups, and the strategies that they employed to cope with, circumvent, and overcome organizational constraints imposed by the state. It concludes with a reflection on the prospects of Church-state encounters in the early twenty-first century.